Polarization toward Tfh2 cell involved in development of MBC and antibody responses against Plasmodium vivax infection. - Pongsakorn Thawornpan; Zulfa Zahra Salsabila; Piyawan Kochayoo; Tipanan Khunsri; Chayapat Malee; Kittikorn Wangriatisak; Chaniya Leepiyasakulchai; Francis Babila Ntumngia; John H Adams; Patchanee Chootong (PLoS Neglected Tropical Diseases)
Background Plasmodium vivax is the dominant Plasmodium spp. causing malaria throughout tropical and sub-tropical countries. Humoral immunity is induced during P. vivax infection. However, data on longevity of antibody and memory B cell (MBC) responses is lacking. Follicular helper T cells (Tfh) are drivers of high-affinity and long-lived antibody responses. Understanding of Tfh-mediated immunity against malaria is valuable for vaccine development. Methodology/principal findings We enrolled 31 acutely infected P. vivax patients in low malaria transmission areas of Thailand to detect frequencies, phenotypes and kinetics of different subsets of circulating Tfh (cTfh) and MBCs, and to evaluate their association with humoral immunity following natural P. vivax infection. Expansion of cTfh2 cells, activated and atypical MBCs were shown during acute malaria. To relate increased cTfh2 cells to humoral immunity, P. vivax-specific MBCs and antibodies were assessed. High anti-PvCSP and -PvDBPII seropositivity was detected and most subjects produced MBCs specific to these antigens. The increased cTfh2 cells were positively related to atypical MBCs, plasmablasts/plasma cells, and anti-PvDBPII IgM and IgG levels. Distributions of memory cTfh cell subsets were altered from central memory (CM) to effector memory (EM) during infection. The highest ratios of cTfh-EM/cTfh-CM were represented in cTfh2 cells. Positive correlation of cTfh17-EM with activated and atypical MBCs was observed, while cTfh2-CM and cTfh17-CM cells were positively related to PvDBPII-specific MBCs and IgM levels. Conclusions/significance Present study demonstrated that P. vivax infection induced cTfh polarization into cTfh2 subset, and alteration of memory cTfh2 phenotype from CM to EM phase. These P. vivax-induced cTfh responses significantly associated with generation of MBCs and antibody responses. Therefore, cTfh2 cells might possibly influence humoral immunity by inducing expansion of activated and atypical MBCs, and by generating P. vivax-specific MBCs and antibody responses following natural infection.